Wanita Sebagai Pondasi Peradaban Perspektif Hadis - Karmilah, Karmilah; Rikaeni, Ike; Yulianti, Ayu; Zainuddin, Ahmad; Mutakin, Mutakin; Muhajir, Muhajir; Ahmad, Lalu Turjiman (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
Women have played a significant role in the history of human civilization, including Islamic civilization. Muslim women such as Khadijah, Aisha, and other female companions (shahabiyah) have made substantial contributions in various fields, including science, propagation of the faith, and activism. However, stigmas against highly educated women persist in certain societies. This research aims to investigate the Hadith perspective on women, education, and their role in Islamic civilization. This qualitative research employs a literature review to gather information. Relevant Hadiths pertaining to the concept of women's education are collected, analyzed deductively and inductively. Education is a fundamental right for all individuals, including women. Women's education is the key to empowering them in various aspects of life. The Hadith underscores the importance of seeking knowledge, especially religious knowledge. This research contributes to a deeper understanding of the crucial role women play in shaping Islamic civilization and addresses the stigma surrounding women's education.